Mothers' amygdala response to positive or negative infant affect is modulated by personal relevance - Strathearn, Lane; Kim, Sohye (Frontiers in Neuroscience, 2013)
Understanding, prioritizing and responding to infant affective cues is a key component of motherhood, with long-term implications for infant socio-emotional development. This important task includes identifying unique characteristics of one’s own infant, as they relate to differences in affect valence—happy or sad—while monitoring one’s own level of arousal. The amygdala has traditionally been understood to respond to affective valence; in the present study, we examined the potential effect of personal relevance on amygdala response, by testing whether mothers’ amygdala response to happy and sad infant face cues would be modulated by infant identity. We used functional MRI to measure amygdala activation in 39 first-time mothers, while they viewed happy, neutral and sad infant faces of both their own and a matched unknown infant. Emotional arousal to each face was rated using the Self Assessment Manikin Scales. Mixed-effects linear regression models were used to examine significant predictors of amygdala response. Overall, both arousal ratings and amygdala activation were greater when mothers viewed their own infant’s face compared with unknown infant faces. Sad faces were rated as more arousing than happy faces, regardless of infant identity. However, within the amygdala, a highly significant interaction effect was noted between infant identity and valence. For own-infant faces, amygdala activation was greater for happy than sad faces, whereas the opposite trend was seen for unknown-infant faces. Our findings suggest that the amygdala response to positive and negative valenced cues is modulated by personal relevance. Positive facial expressions from one’s own infant may play a particularly important role in eliciting maternal responses and strengthening the mother-infant bond.